A STUDY OF THE IMAGE QUALITY OF COMPUTED TOMOGRAPHY ADAPTIVE STATISTICAL ITERATIVE RECONSTRUCTED BRAIN IMAGES USING SUBJECTIVE AND OBJECTIVE METHODS. Issue 1 (7th June 2016) - Mangat, J.; Morgan, J.; Benson, E.; Båth, M.; Lewis, M.; Reilly, A.
Abstract : The recent reintroduction of iterative reconstruction in computed tomography has facilitated the realisation of major dose saving. The aim of this article was to investigate the possibility of achieving further savings at a site with well-established Adaptive Statistical iterative Reconstruction (ASiR™) (GE Healthcare) brain protocols. An adult patient study was conducted with observers making visual grading assessments using image quality criteria, which were compared with the frequency domain metrics, noise power spectrum and modulation transfer function. Subjective image quality equivalency was found in the 40–70% ASiR™ range, leading to the proposal of ranges for the objective metrics defining acceptable image quality. Based on the findings of both the patient-based and objective studies of the ASiR™/tube–current combinations tested, 60%/305 mA was found to fall within all, but one, of these ranges. Therefore, it is recommended that an ASiR™ level of 60%, with a noise index of 12.20, is a viable alternative to the currently used protocol featuring a 40% ASiR™ level and a noise index of 11.20, potentially representing a 16% dose saving.